The use of RADARSAT-1 imagery for lithological and structural mapping in the Canadian High Arctic. - Riopel, Simon. (University of Ottawa (Canada), 2000)
RADARSAT-1 images of the northern part of Axel Heiberg Island were acquired to define a selection of preferable beam modes for geological mapping in this cold and arid environment with locally rugged topography. Fine, Standard, and Extended High beam mode images with different resolutions, areas of coverage, look directions, incidence angles, and dates of acquisition were analyzed in this study. Major geological contacts in this part of the Sverdrup Basin and the Franklinian Mobile Belt are well identified in these images. Numerous post-Paleozoic tabular intrusive bodies were also identified. Although shadowing and other geometric effects were accentuated, structural features and lineaments were best highlighted in RADARSAT-1 images with higher incidence angles where less topographic displacement is present. Significant seasonal changes in radar image tone associated with localized melting of the active layer were clearly visible between winter and summer images. RADARSAT-1 beam modes were successfully used to make stereo-pairs. (Abstract shortened by UMI.)
Keywords: Physical Geography.